Pengaruh Fasilitas, Minat dan Motivasi Terhadap Pengembangan Kompetensi Mahasiswa di Masa Pandemic Virus Corona-19 - Syardiansah Syardiansah; Safuridar Safuridar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Student competence is one of the final goals to be achieved by higher education. High competence will be able to provide great opportunities for students to win the competition in this day and age. In education a number of things are able to develop competencies including educational facilities, students' interests and motivation. This study aims to determine the effect of facilities, interests and motivation on student competencies during the Corana virus. When the corona virus took place, the distance lecture was implemented, where students and lecturers did not meet directly during the education process. Based on the results of the study it was found that partially the facility had a positive and significant effect on the development of student competencies with a tig value of 0,000 <0.05. Interest in pasial has a significant and positive effect on the development of student competencies with a t-sig value of 0.005 <0.05. And the motivational variable has a positive and significant effect on the development of student competencies with a tig value of 0.004 <0.05. Simultaneously variable facilities, interests and motivation have a positive and significant effect on the development of student competencies with a F sig value of 0,000 <0.05. The coefficient of determination of 0.452 means that the facilities, interests and motivation variables have 45.2% of the development of student competencies.